Implementasi terhadap Teknologi Informasi dan Komunikasi dalam Penguatan Nilai-Nilai Islam di Pesantren Daarul Putra Madinah - Siti Nurdiana Wijaya; Putri Aulia Harahap; Putri Ayu Ningsih; Novianty Khairani; Victor Asido Elyakim P (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
Daarul Putra Madinah Islamic Boarding School has an important role in producing a generation that is noble and knowledgeable in accordance with Islamic values. However, the challenges of the digital era present an urgent need for the pesantren to integrate information and communication technology (ICT) in its education system. This pesantren faces several obstacles, such as limited digital resources, lack of understanding of technology among students and teachers, and less than optimal technology-based learning methods in supporting the understanding of Islamic values. This implementation activity aims to strengthen Islamic values through a digital approach that is more effective and relevant to the times. The activity steps include digital literacy training, multimedia-based Islamic content development, and the application of information and communication technology (ICT)-based learning applications. The expected result is an increase in the capacity of pesantren in utilizing technology to strengthen religious learning, while instilling Islamic values in a more interactive and contextual manner. With the implementation of this activity, pesantren are expected to be able to answer the challenges of modernization without sacrificing the essence of Islamic values, while creating a more inclusive, interesting, and relevant learning environment for santriDaarul Putra Madinah Islamic Boarding School has an important role in producing a generation that is noble and knowledgeable in accordance with Islamic values. However, the challenges of the digital era present an urgent need for the pesantren to integrate information and communication technology (ICT) in its education system. This pesantren faces several obstacles, such as limited digital resources, lack of understanding of technology among students and teachers, and less than optimal technology-based learning methods in supporting the understanding of Islamic values. This implementation activity aims to strengthen Islamic values through a digital approach that is more effective and relevant to the times. The activity steps include digital literacy training, multimedia-based Islamic content development, and the application of information and communication technology (ICT)-based learning applications. The expected result is an increase in the capacity of pesantren in utilizing technology to strengthen religious learning, while instilling Islamic values in a more interactive and contextual manner. With the implementation of this activity, pesantren are expected to be able to answer the challenges of modernization without sacrificing the essence of Islamic values, while creating a more inclusive, interesting, and relevant learning environment for santri.